Persuasive Technology 8th International Conference, PERSUASIVE 2013, Sydney, NSW, Australia, April 3-5, 2013. Proceedings - Berkovsky, Shlomo; Freyne, Jill.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 8th International Conference on Persuasive Technology, PERSUASIVE 2013, held in Sydney, NSW, Australia, in April 2013. The 16 revised full papers and 12 revised short papers presented were carefully reviewed and selected from 47 submissions. The papers address not only typical persuasive domains like health and environment, but also cover emerging research topics, such as data safety and evaluation of persuasive technologies.
Keywords: Computer science; Medical records -- Data processing; Multimedia systems; Computer Science; Health Informatics; User Interfaces and Human Computer Interaction; Multimedia Information Systems; Information Systems Applications (incl. Internet).; Computers and Society